Development of a mobile app for technology-enhanced learning (TEL) of combinatorial logic circuits - Ang, Liang (Nanyang Technological University, 2023)
The goal of the project is to develop a mobile app that can help enhance the learning of combinatorial logic circuits, such as decoders and multiplexers. The main function of the app is to automatically generate a set of combinatorial logic questions for practice and provide verification that the answers inputted by users are correct. The app is also designed to be interactive with multiple methods of answering questions such as text input, multiple choice and a dropdown picker. Additional functions such as study notes is also included. The application is built using React Native, a JavaScript framework used for developing cross platform applications. Backend development is done using the Firebase application programming interface.